2018
DOI: 10.1523/jneurosci.2433-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to Pain: A Peripheral Component Identified Using Induced Pluripotent Stem Cells and Dynamic Clamp

Abstract: Pain is a complex process that involves both detection in the peripheral nervous system and perception in the CNS. Individual-toindividual differences in pain are well documented, but not well understood. Here we capitalized on inherited erythromelalgia (IEM), a well characterized human genetic model of chronic pain, and studied a unique family containing related IEM subjects with the same disease-causing Na V 1.7 mutation, which is known to make dorsal root ganglion (DRG) neurons hyperexcitable, but different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 41 publications
4
103
0
Order By: Relevance
“…Multiple modulatory factors can shape the pain experience of patients carrying Nav1.7 gain‐of‐function mutations; for example, a recent study of two patients with IEM both carrying the same Nav1.7mutation but with different pain profiles, demonstrated that a variant of a second gene, in a potassium channel, can introduce a degree of resilience to pain . Moreover, Nav1.7 mutations may affect multiple cell types including some cells outside the nervous system.…”
Section: Epidemiologymentioning
confidence: 99%
“…Multiple modulatory factors can shape the pain experience of patients carrying Nav1.7 gain‐of‐function mutations; for example, a recent study of two patients with IEM both carrying the same Nav1.7mutation but with different pain profiles, demonstrated that a variant of a second gene, in a potassium channel, can introduce a degree of resilience to pain . Moreover, Nav1.7 mutations may affect multiple cell types including some cells outside the nervous system.…”
Section: Epidemiologymentioning
confidence: 99%
“…iPSC-Noc cells from both subjects were hyperexcitable. However, there was a lower level of excitability in the iPSC-Noc from the patient with pain resilience, and a GOF mutation in Kv7.2 potassium channels was found to be responsible (Mis et al, 2019). Both studies highlight the utility of iPSC-derived nociceptors for pain research.…”
mentioning
confidence: 86%
“…McDermott et al (2019) used iPSC-Noc to assess the impact of Na V 1.7 LOF mutations on electrogenesis and also to study channel trafficking and pharmacology. Mis et al (2019) recently studied iPSC-Noc from a pair of IEM patients carrying the same Na V 1.7 mutation, with one patient manifesting severe pain and the other manifesting pain resilience. iPSC-Noc cells from both subjects were hyperexcitable.…”
mentioning
confidence: 99%
“…They performed a comparative study on three members of a family affected by IEM: a mother, a father, and a son. The mother and the son both harbor a Na v 1.7 mutation (Na v 1.7-S241T) and experience IEM symptoms, but the pain profile of the son is considerably more severe (Geha et al, 2016;McDonnell et al, 2016;Mis et al, 2019). The father lacks the mutation and is unaffected by IEM.…”
mentioning
confidence: 99%